2020
DOI: 10.1101/2020.02.24.962522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Intergenic Small Non-Coding RNAittAis Required for Optimal Infectivity and Tissue Tropism inBorrelia burgdorferi

Abstract: ABSTRACTPost-transcriptional regulation via small regulatory RNAs (sRNAs) has been implicated in diverse regulatory processes in bacteria, including virulence. One class of sRNAs, termed trans-acting sRNAs, can affect the stability and/or the translational efficiency of regulated transcripts. In this study, we utilized a collaborative approach that employed data from infection with the Borrelia burgdorferi Tn library, couple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 108 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…It is possible that the promoter region of the downstream gene is within the coding region of the GOI and therefore replacement of GOI with resistance marker will impact the levels of the downstream gene. In addition, it has been recently shown that there is a likelihood of small RNA (sRNAs) and non‐coding RNA (ncRNAs) within the intergenic regions that can have localized or distal effects on gene expression profile impacting the overall phenotype observed with the transformants (Arnold et al., 2016; Arnold et al., 2018; Lybecker & Samuels, 2017; Medina‐Perez et al., 2020). These considerations should be factored into how the deletion construct is generated using suicide vectors as shown in Figures 1‐2.…”
Section: Strategic Planningmentioning
confidence: 99%
“…It is possible that the promoter region of the downstream gene is within the coding region of the GOI and therefore replacement of GOI with resistance marker will impact the levels of the downstream gene. In addition, it has been recently shown that there is a likelihood of small RNA (sRNAs) and non‐coding RNA (ncRNAs) within the intergenic regions that can have localized or distal effects on gene expression profile impacting the overall phenotype observed with the transformants (Arnold et al., 2016; Arnold et al., 2018; Lybecker & Samuels, 2017; Medina‐Perez et al., 2020). These considerations should be factored into how the deletion construct is generated using suicide vectors as shown in Figures 1‐2.…”
Section: Strategic Planningmentioning
confidence: 99%
“…In this study, we attempted to further characterize the bbd07/SR0726 locus of lp17 by determining whether the functional product encoded by this intergenic region is an RNA or protein, and assessing any potential regulatory effects resulting from its targeted investigators (44). We reasoned that a regulatory sRNA may have drastic effects on multiple bacterial characteristics if it were transcribed from a high-copy plasmid, and that investigation of these effects could provide insight into the native function of ittB.…”
Section: Discussionmentioning
confidence: 99%
“…B. burgdorferi B31 gene annotations were downloaded from NCBI, RefSeq assembly accession GCF_000008685.2. sRNA annotations (Supplementary Table 2), as outlined above, were merged and sRNA gene names included for ssrA /tmRNA (SR0030), ssrS (6S) (SR0136) (Drecktrah et al, 2020), rnpB (SR0613), BsrW (SR0412) (Arnold et al, 2016), and IttA (SR0736) (Medina-Perez et al, 2020). The following sRNAs were missed from Supplementary Table 2 because of a lack of a 3′/5′ end within 75 nt of the previous sRNA annotations and were manually added: srp , ffs (4.5S) (SR0360), DsrA (SR0440) (Lybecker and Samuels, 2007) and IttB (Crowley and Bankhead, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…B. burgdorferi RNA-mediated regulation has not been well characterized. Two putative base-pairing sRNAs have been suggested to have regulatory roles and/or impact infectivity (Lybecker and Samuels, 2007; Medina-Perez et al, 2020), but their direct base- pairing function has not been demonstrated. Further, no cis- acting RNAs have been described in B. burgdorferi .…”
Section: Introductionmentioning
confidence: 99%